Conversion to Islam of one parent: effects to the religion of the child / Khairul Aisamuddin Abdul Rahman and Zainab Hanis Zulkifli - Abdul Rahman, Khairul Aisamuddin; Zulkifli, Zainab Hanis (2012)
This research looks into the Malaysian laws which govern the religious rights of a child when one parent converts to Islam and the approaches and practices of various religious departments in the issue of the religion of the children of one Muslim spouse in a non-Muslim marriage. Therefore this research analyses the civil and Syariah law perspective on conversion of religion in order to expose its incomprehensiveness. This research aims to reform the current laws governing the religious rights of a child in circumstances when one parent converted to Islam. By using the doctrinal and empirical research method, this research looks into the effect of conversion of one parent to Islam on the religion of the child with reference to the guidelines that have been used in local and foreign jurisdiction. In the absence of comprehensive discussion on the religion of the child in the event of the conversion of religion of one spouse, this research is to fill in the gap. It is proposed that a few laws need to be amended to solve the problems that arise relating to the religion of a child due to the conversion of one parent to Islam. When there is a dispute on the religion of the child, the parties should be referred to a mediation session. The religion of the child remains the same according to the common religion of both the parents prior to the conversion until he or she turns 18 years old.